The Role of Business Education in Promoting Social Entrepreneurship and Poverty Alleviation in Low-Income Communities - Suherlan, Suherlan; Az Zaakiyyah, Hizbul Khootimah; Ahmad, Muh. Ihsan Said (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Poverty alleviation remains one of the global challenges that continue to be a primary focus in the sustainable development agenda. Social entrepreneurship emerges as a business model with the potential to provide sustainable solutions through innovative approaches and an orientation towards achieving social benefits. This research aims to analyze the role of education in promoting social entrepreneurship and poverty alleviation in low-income communities. The research methodology encompasses the approaches used in the literature review. A qualitative approach is the main focus to gain deep insights into this topic. The data used comes from reliable sources, namely Google Scholar, covering the period 2001-2024. The study results show that business education has significant potential in promoting social entrepreneurship and alleviating poverty in low-income communities. To achieve this, a holistic approach is needed that includes the integration of social entrepreneurship principles into the curriculum, development of practical skills through hands-on experience, collaboration among stakeholders, policy support, and strong impact measurement.